Increased self-regulation of eating behavior is associated with reduced generalized anxiety disorder in Saudi Arabia - Ghabashi, Mai Adil (Frontiers in Psychology, 2024)
Introduction There is a growing body of evidence suggesting that self-regulation of eating behavior (SREB) is closely linked to dietary habits and mental health. However, little is known about these relationships within the Saudi Arabian population. This study aimed to address this gap. Methods A digital cross-sectional study was conducted utilizing the SREB and generalized anxiety disorder (GAD-7) questionnaires, along with a brief survey about dietary habits. Linear and logistic regression analyses were employed to examine these associations, with a total of 651 Saudi participants enrolled in the study. Results The results showed that only 15.5% of participants demonstrated a high capacity for SREB, while 65% experienced moderate or severe symptoms of GAD. Greater SREB was significantly associated with reduced GAD scores (β = −0.13, 95% CI; −0.12 to −0.03; p < 0.001) and lower BMI (β = −0.10, 95% CI; 0.08 to −0.00; p = 0.01). Additionally, predictive factors for high capacity for SREB included higher daily intake of fruits (OR = 2.90, 95% CI; 1.44 to 5.84; p = 0.003) and regular breakfast consumption (OR = 1.64, 95% CI; 1.01 to 2.63; p = 0.04). Discussion These findings suggest that enhancing SREB may be a promising strategy for obesity prevention and improving mental health outcomes among the Saudi population. Implementing interventions aimed at promoting healthier dietary habits could support the physical and mental well-being of this population.